P7: POSTPARTUM DEPRESSION POSITIVE SCREEN PREDICTORS IN A PEDIATRIC ED. Issue 3 (March 2016) - Jarvis, L; Badolato, G; Breslin, K; Goyal, M
Abstract : Purpose of Study: The World Health Organization (WHO) and Toronto Public Health (TPH) performed a systematic literature review to identify predictors for different risk categories for postpartum depression (PPD). This review did not include patients in the pediatric emergency department (PED) setting. This study determines if the predictors identified in the WHO/TPH review are associated with positive PPD screens in an urban PED. Methods Used: We performed a prospective, cross-sectional survey of a convenience sample of mothers presenting with low-acuity triage level infants </=six months old to a PED. We calculated frequency of positive PPD screen predictors and performed multivariable logistic regression to identify association with a positive PPD screen. Summary of Results: 121 mothers were screened for PPD during presentation to the PED with their infant; 27 (22%) screened positive. Adjusting for maternal age, race/ethnicity, and insurance status, WHO/TPH "strong" predictors of a previous history of depression (aOR 6.7; 95% CI 1.6, 28.6), a previous history of anxiety (aOR 16.1; 95% CI 2.1, 125.5), depressed mood or anxiety during this pregnancy (aOR 25.6; 95% CI 6.7, 98.2), a recent stressful life event (aOR 5.4; 95% CI 1.9, 15.2), and lack of social support (report that they did not have someone they could count on to help with the baby; aOR 6.5; 95% CI 1.6, 26.9) were significantly associated with a positive PPD screen. "Moderate" predictors of infant fussiness, (all/most of the time; aOR 8.4; 95% CI 2.0, 35.3) and high levels of childcare stress (all/most of the time; aOR 4.6; 95% CI 1.7, 12.4) were significantly associated with a positive screen. "Small" predictors of quality of relationship with the partner (sometimes vs. all/most of the time having a good relationship with the partner; aOR 3.8; 95% CI 1.0, 6.3) was significantly associated; obstetric and pregnancy complications and socioeconomic status were not significantly associated. Our study was consistent with the WHO/TPH review which found no association of PPD with ethnicity, maternal age, education level, parity, or gender of the child. Conclusions: Results in this urban PED are largely consistent with WHO/TPH predictors of PPD developed in other settings. Understanding PPD predictors can help physicians to improve screening and identification of PPD positive mothers.